Teorema Kekonvergenan Fungsi Terintegral Henstock-Kurzweil Serentak dan Fungsi Bersifat Locally Small Riemann Sums (LSRS) - Aniswita Aniswita (Universitas Islam Negeri (UIN) Mataram, 2013)
In this paper we discuss Henstock Equi a-integrable and Uniformly Locally Small Riemann Sums (UESRS) properties for Henstock-Kurzweil integrable functions from the Euclidean spaces into the Sequences space